2010
DOI: 10.2478/s11687-010-0033-8
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Metastrongylidae in wild boars from southern Poland

Abstract: SummaryOf 25 wild boars (Sus scrofa) collected in southern Poland during the winter season of 2009/2010 and examined for lung nematodes, 20 (80.0 %) were concominantly infected, and the mean ± SD intensity reached 84.8 ± 67.6 (range 7 -250) parasites. From the whole of 1695 gathered Metastrongylidae specimens, 1121 (66.1 %) were distinguished to five species: Metastrongylus pudendotectus, M. salmi, M. asymmetricus, M. elongatus and M. confusus. The species ratios were 3.4:2.7:1.5:1.1:1.0, respectively, with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 12 publications
6
10
1
2
Order By: Relevance
“…Although in previous studies (Gallazzi, 1977;Nosal et al, 2006) cyclical variations in the excretion of intestinal Eimeria oocysts in rabbits appeared to be mostly affected by the seasonal period, no differences emerged in the present study from the comparison of data observed in examined female rabbits in the 2 different periods of the year following the first (in May) and second (in November) parturitions. Therefore, other factors that occur during the periparturient period should be responsible for the faecal oocysts shedding observed in examined female rabbits.…”
Section: Discussioncontrasting
confidence: 46%
“…Although in previous studies (Gallazzi, 1977;Nosal et al, 2006) cyclical variations in the excretion of intestinal Eimeria oocysts in rabbits appeared to be mostly affected by the seasonal period, no differences emerged in the present study from the comparison of data observed in examined female rabbits in the 2 different periods of the year following the first (in May) and second (in November) parturitions. Therefore, other factors that occur during the periparturient period should be responsible for the faecal oocysts shedding observed in examined female rabbits.…”
Section: Discussioncontrasting
confidence: 46%
“…In imported wild boars, different parasitic species (Oesophagostomum dentatum, Ascaris suum and Trichuris suis) were identified, which had not existed in central Spain. Similar observations were reported in Poland, where the types and prevalence of helminths in wild boars in the northwestern region of Poland (21) were different from the findings in central Poland (7). Such findings correspond with the results reported in Serbia, where helminth fauna in wild boars significantly differed between the hunting grounds in North Backa, Braničevo (South Serbia) and Belgrade area (Central Serbia) (4,26,27,34).…”
Section: Discusionsupporting
confidence: 84%
“…The European research on wild boar helminths resulted in a list of 30 species, encompassing flukes, tapeworms, nematodes, and acanthocephalans, as well as their larvae. Examinations performed in Germany (2,3,18), France (13), Hungary (35) and in Czech Republic and Slovakia (1,21) indicated that the helminth and protozoa species which we found usually occurred in wild boars in Europe. The importance of testing wild boars for the presence of endoparasites has been gaining increasing attention taking into account the importance of parasites for domestic pigs and the losses and damage they can cause, as well as the problems related to management and its effects on pig production.…”
Section: Discusionmentioning
confidence: 68%
“…in this study was 196.5 nematodes per lung and, like for the prevalence, worm burdens were larger in northern wild boars (218.0, with up to 2895 specimens in a single animal) compared to southern animals (157.4, maximum 597 specimens/animal), although this difference was not significant. Overall, these numbers were significantly higher compared to the ones obtained from wild boars of other European countries, varying from 6.3 to 96.2%, reviewed in Table 5 ( de-la-Muela et al, 2001 ; Fernandez-de-Mera et al, 2003 ; García-González et al, 2013 ; Jä;rvis et al, 2007 ; Nosal et al, 2010 ; Poglayen et al, 2016 ). In a study from Spain, lungworm burden of imported captive bred wild boars were much higher than in the autochthonous, free-ranging population, with a mean burden of 633 nematodes per lung ( Fernandez-de-Mera et al, 2003 ).…”
Section: Discussionmentioning
confidence: 58%